Development of nanocomposite dielectric materials for high energy density capacitor applications - Lin, Meng-Fang (2013)
In the recent years, an immense interest has been generated on developing suitable dielectric materials for high electric energy storage. Ferroelectric ceramic materials exhibit very high dielectric constant but they are brittle and possess low dielectric strength. On the other hand, polymer materials are flexible with high ease of processing at low processing temperatures, and possess high dielectric breakdown field. By combining these two materials, one can develop an improved material system with higher dielectric constant and higher breakdown field to realize the high energy storage density. Barium titanate (BaTiO3) is widely used in electronic devices such as multi layer ceramic capacitor and other electronic devices due to its superior dielectric characteristics. Structure distortion via doping has been used to modulate the physical properties of BaTiO3. In this work, single crystalline Nd-doped BaTiO3 hollow nanoparticles have been synthesized via a simple hydrothermal method. With unique hollow structured morphology, the nanoparticles not only exhibited excellent compatibility with poly (vinylidene fluoride) (PVDF), but showed significant enhancement of the dielectric properties of the nanocomposites. Design and optimization of the synthesis method have been achieved through a systematic study. The formation of hollow nanostructures is proposed to follow a Kirkendall induced hollowing mechanism which is governed by the differences in diffusion rates of dopant ions, water molecules and core ions during the synthesis reaction. The differences in the surface characteristics of ceramic fillers and polymer matrix in the nanocomposite system cause non-uniform dispersion in the polymer matrix which affects electrical properties. We studied the surface functionalization of BaTiO3 nanoparticles with dopamine using reflux method to strongly bind dopamine with hydrogen bonding on BaTiO3 nanoparticle surface and improve its compatibility with PVDF polymer matrix. FT-IR spectra were used to confirm the successful surface functionalization of BaTiO3 nanoparticles after immobilization with dopamine. SEM characterizations showed that the nanoparticles dispersed uniformly after the dopamine modification and void formation in the nanocomposite films has been lowered. Electrical properties of the resultant nanocomposite showed that the dielectric constant can be enhanced greatly with low dielectric loss There are several types of methods to prepare nanocomposites such us solution mixing, simple blending methods. Sample preparation method has a strong effect on the dispersion of nanoparticles into polymer matrices and phase separation which will in turn influence the electrical properties of the nanocomposite. Fillers are not easy to disperse homogeneously into fluorinated polymer matrix due to its chemical inertness. We developed novel in-situ synthesis methods to prepare core-shell structured ceramic-polymer nanocomposites in which the dielectric nanoparticle shell is attached well on to the insulating polymer core surface to prevent aggregation of nanoparticles. The core-shell structured ceramic-polymer nanocomposite was developed using two different types of cross-linking agents via in-situ synthesis method without any catalyst and initiators. We demonstrated that in-situ synthesis of nanocomposite using cross-linking agents not only enables highly uniform dispersion of the fillers to form core-shell structure nanocomposite but also improves electrical properties remarkably.